Synthesis and Characterization of Titanium Dioxide/Graphene Nanoplatelets Nanocomposites via Planetary Ball Milling for Military Radar Absorbing Materials - Gita Resty Amalia; Andri Hardiansyah; Anselmo Bima Rasendriya; Ismail Rahmadtullah; Andi Setiono; Riri Murniati (Indonesian Scholar Society, 2025)
Stealth technology is widely used in the military field to avoid enemy detection. Consequently, there has been a significant surge in research related to radar-absorbing materials (RAMs). Titanium dioxide (TiO2) and graphene nanoplatelets (GNPs) are promising materials for developing RAMs. Combining TiO2 as a semiconductor with GNPs as a conductive material could increase the ability to absorb microwaves through a more effective energy dissipation mechanism. In our study, TiO2 and GNPs were fabricated using the planetary ball milling method. The structure and morphology of the resulting nanocomposites were evaluated using Field Emission Scanning Electron Microscopy with Energy Dispersive Spectroscopy with Energy Dispersive Spectroscopy (FE-SEM EDS) and X-ray Diffraction (XRD). FE-SEM observations showed that TiO2 nanoparticles were attached to the surface of layered GNPs. XRD analysis showed a decrease in the peak intensity of the TiO2/GNP nanocomposites compared to pure TiO2 due to the addition of carbon elements. The performance of RAMs was evaluated using a Vector Network Analyzer (VNA) in the X-band (8-12 GHz) range with a 3-mm thickness. The VNA analysis indicated that the TiO2/GNP nanocomposites exhibited the optimal reflection loss (RL) of -30.72 dB at a frequency of 8.42 GHz, accompanied by a through power of 99.91%. Consequently, TiO2/GNP nanocomposites demonstrated promising potential as a military RAM.